TINGKAT LITERASI KEUANGAN DI KALANGAN MAHASISWA STIE MUSI - Anastasia Sri Mendari; Suramaya Suci Kewal (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2013)
Abstrak: Tingkat Literasi Keuangan di Kalangan Mahasiswa STIE Musi. Penelitian ini bertujuan untuk mengetahui bagaimana tingkat literasi keuangan mahasiswa STIE Musi itu. Aspek yang diteliti adalah: pengetahuan tentang keuangan pribadi, simpan pinjam, asuransi, dan investasi. Populasi dalam penelitian ini adalah mahasiswa yang mengisi Kartu Rencana Studi STIE Musi di semester I tahun akademik 2012/2013. Responden pada penelitian ini sebanyak 305. Hasil penelitian mengindikasikan bahwa untuk keputusan keuangan berdasarkan pendapat pribadi, dalam beberapa hal mencerminkan kurangnya pengetahuan tentang bentuk-bentuk investasi jangka panjang yang memberikan imbal hasil dan risiko yang lebih tinggi dari deposito, serta keputusan untuk asuransi jiwa, responden tidak mengerti asuransi jiwa. Keyword: literasi keuangan, investasi, life insurance Abstract: Level of Financial Literacy among STIE Students Musi. This study aims to know how the level of financial literacy of STIE Musi’s students. Aspects investigated are: knowledge of personal finance in general, savings and loans, insurance, and investments. The population in this study were college students who fill out STIE Musi’s Card Study Plan of first semester of academic year 2012/2013. 305 respondents were surveyed. The results showed that for every observable aspect of respondents could be correctly categorized as low as scores of less than 60%. For financial decisions based on personal opinion, in some ways reflects the lack of knowledge of other forms of long-term investments that provide returns and higher risk than deposits, as well as the decision for life insurance, the respondents do not understand life insurance. Keyword: financial literacy, investment, asuransi jiwa